2019
DOI: 10.1007/s11111-019-00333-6
|View full text |Cite
|
Sign up to set email alerts
|

Ambient temperature, birth rate, and birth outcomes: evidence from South Korea

Abstract: The effects from rising temperatures, a symptom of climate change, have become a significant concern. This study finds that one additional day with a maximum temperature of 30-32°C (86-89.6°F), relative to a day with a temperature of 28-30°C (82.4-86°F), decreases the birth rate 9 months later by 0.24%, or 92 babies per month in South Korea. This result is robust to various specifications and samples. This study also found that the impact of the temperature bin did not vary according to the mother's characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Preterm birth was identified as a major outcome variable in 44 articles (Table 3 [17,19,20,24,25,28,31,33,35,37,[42][43][44][45]48,52,54,55,57,58,63,64,66,67,[71][72][73]76,[79][80][81][83][84][85][86][87][88][90][91][92][93][96][97][98]). Most studies implemented a cohort (17), time-series, registry (11) or population registry (10) design, and described positive associations (40) between environmental heat exposures and preterm birth.…”
Section: Preterm Birthmentioning
confidence: 99%
See 1 more Smart Citation
“…Preterm birth was identified as a major outcome variable in 44 articles (Table 3 [17,19,20,24,25,28,31,33,35,37,[42][43][44][45]48,52,54,55,57,58,63,64,66,67,[71][72][73]76,[79][80][81][83][84][85][86][87][88][90][91][92][93][96][97][98]). Most studies implemented a cohort (17), time-series, registry (11) or population registry (10) design, and described positive associations (40) between environmental heat exposures and preterm birth.…”
Section: Preterm Birthmentioning
confidence: 99%
“…See reference list for 44 studies included in analysis[17,19,20,24,25,28,31,33,35,37,[42][43][44][45]48,52,54,55,57,58,63,64,66,67,[71][72][73]76,[79][80][81][83][84][85][86][87][88][90][91][92][93][96][97][98].1 Several studies included temperature exposures up to month prior to delivery in analysis; included in 2nd/3rd trimester 2. Ha et al, 2017, included multiple exposure periods from 1st/2nd trimesters in analysis[44]-included in any part of pregnancy.…”
mentioning
confidence: 99%
“…However, to date, evidence remains limited (Kloog et al 2015;Zhang, Yu, and Wang 2017;Basu et al 2018), and that which is available is somewhat mixed. For example, a recent analysis of data from Korea found no significant temperature effect on birth outcomes (Cho 2020). A systematic review published in 2017 concluded that the evidence linking preterm birth and low birth weight to ambient temperature was still very limited and not yet conclusive, though there were more examples of adverse estimated effects for high temperatures than for low temperatures (Zhang, Yu, and Wang 2017).…”
Section: Extreme Temperature and Birth Outcomesmentioning
confidence: 99%
“…Ambient environmental conditions, including both air pollution and temperature, have been associated with adverse birth outcomes in a number of settings, though findings for temperature remain limited (Shah and Balkhair 2011;Stieb et al 2012;Klepac et al 2018;Melody et al 2019;Cho 2020;Kloog et al 2015;Zhang, Yu, and Wang 2017). There is some suggestive evidence that lower socioeconomic status groups, defined by occupation or education, might be distinctly vulnerable to the ill effects of air pollution or extreme temperatures, but there is a need for additional studies to consider possible mitigation of negative effects by maternal education (see Basu et al (2018) and Son et al (2019) for contradictory findings on temperature and birth weight; for a review of findings on pollution and low birth weight, see Westergaard et al (2017)).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this long-standing interest, causal estimation of the relationship between temperature and overall conception rates is missing. Existing studies have only examined the effect of temperature on live birth rates, and they have found that exposure to hot temperature causes a decline in birth rates 9-10 months later (Seiver 1989;Lam and Miron 1996;Barreca et al 2018;Cho 2020). Barreca et al (2018) also have found that this decline is followed by a partial rebound in the next 3 months.…”
Section: Introductionmentioning
confidence: 99%